Characteristics of urinary tract infections in children up to 7 years of age - Biljana Milinković; Dejan Bokonjić; Bojan Joksimović; Vojo Kulić; Veselinka Šupić (Биомедицинска истраживања, 2018)
Urinary tract infection (UTI) is defined as a presence of significant bacteriuria in a properly collected urine sample, followed by various clinical manifestations - from asymptomatic bacteriuria to acute pyelonephritis. It is most common in infancy and particularly in females. There is a higher risk of UTI in children with underlying urological anomalies, voiding dysfunction and constipation. The subsequent long-term complications such as hypertension and chronic renal insufficiency might arise in children with recurrent pyelonephritis due to renal scarring. The early and proper diagnosis of UTI needs to be based on the recognition of clinical signs and symptoms of UTI, microscopic examination of urine sediment, urine culture and radiological findings. The objective of various medical imaging studies, including kidney and bladder ultrasound, voiding cystourethrography and technetium-99m-dimercaptosuccinic acid renal scintigraphy, is to identify urinary tract abnormalities, as well as risk factors for recurrent infections. The UTI that has been diagnosed requires a 7-14-day course of antimicrobial therapy in symptomatic and especially febrile children. In most children, the early diagnosis and treatment of recurrent UTI is of utmost importance. In this way the development of permanent kidney damage, as well as permanent consequences will be prevented.
Keywords: urinary tract infections; children; diagnosis; treatment